The different effects of Chinese Herb Solid Drink and lactulose on gut microbiota in rats with slow transit constipation induced by compound diphenoxylate. (May 2021) - Deng, Zhitong; Fu, Zhuotao; Yan, Wen; Nie, Kechao; Ding, Lingli; Ma, Duanhua; Huang, Haodong; Li, Tao; Xie, Jianxing; Fu, Linchun
Graphical abstract: Highlights: CHSD and lactulose ameliorate STC through different mechanisms. CHSD has a better effect on community diversity and richness than lactulose. CHSD and lactulose result in differences in the SCFA composition in faeces. CHSD and lactulose elevate stimulatory neurotransmitters and reduce VIP in serum. Abstract: Slow transit constipation (STC) has become an epidemic medical problem. There are several kinds of drugs for constipation; however, each drug has its limitations. The gut microbiota has a close relationship with STC. Lactulose is an effective drug for constipation because it is a kind of bulking laxative and microbioecologic, and it relieves the syndromes of STC. We found that the Chinese Herb Solid Drink (CHSD), which contains medicine food homologous materials such as psyllium husk, sweet almond, semen sesami nigrum, and hemp seed, has a similar effect on relieving constipation as lactulose, although it has different effects on the gut microbiota. We investigated the mechanisms of CHSD in rats with STC, induced by diphenoxylate, via constipation index and enzyme linked immunosorbent assay (ELISA) analyses using serum and 16S rDNA amplicon and gas chromatography-mass spectroscopy (GC–MS). CHSD enhanced the relative abundance of some types of gut microbiota, such as Blautia, Ruminococcus, Roseburia, Coprococcus, Lachnospira, and Phascolarctobacterium, while lactulose enhanced the relative abundance of Blautia, Phascolarctobacterium, Eubacterium, and Akkernansia in diphenoxylate-induced STC rats. Both CHSD and lactulose enhanced the level of short-chain fatty acids in the faeces of rats; however, the composition of those were different between the two drugs. From the perspective of the gut neuroendocrine system, both CHSD and lactulose could elevate neurotransmitters, such as motilin (MTL) and substance P (SP), which promote intestinal peristalsis and reduce the expression of vasoactive intestinal peptide, which inhibits intestinal peristalsis in the serum of STC rats. CHSD could elevate gastrin expression, which also promoted intestinal peristalsis in serum, while lactulose did not have this effect. Our findings suggest that CHSD may be an effective and safe therapeutic choice for STC.